PENGARUH CITRA MEREK DAN KATA ELEKTRONIK DARI MULUT KE MULUT TERHADAP LOYALITAS PELANGGAN PENGGUNA PRODUK KOSMETIK EMINA COSMETICS - Utami Dea Putri; Nino Nopriandi (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
Market needs and wants that move dynamically change rapidly and continuously, companies must be more creative in interpreting the threats and opportunities that exist in the market through the utilization of the company's strengths and capabilities. Cosmetics in Indonesia continues to experience increasing demand for cosmetics, which encourages many cosmetic industries to continue to compete in creating products with the advantages possessed by each company and innovations that can attract purchasing decisions. Local cosmetic products and equipment that are widely available in supermarkets, department stores, cosmetic centers as well as those offered from the internet are increasingly diverse and the choices are increasingly varied. This study aims to analyze the simultaneous and partial effect of brand image and eworm on customer loyalty using Emina cosmetic products. The method used is quantitative method using regression analysis. This study involved 50 research respondents. The results of the study reveal that there is a partial or simultaneous influence of brand image and eworm on customer loyalty.